1995
DOI: 10.1212/wnl.45.6.1193
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term dichloroacetate treatment improves indices of cerebral metabolism in patients with mitochondrial disorders

Abstract: We performed a short-term, double-blind, placebo-controlled, crossover trial of sodium dichloroacetate (DCA) therapy in 11 patients affected by various primary mitochondrial disorders. Independent measures of oxidative metabolism (venous blood metabolites, exercise testing, phosphorus magnetic resonance [MR] spectroscopy of muscle, and proton MR spectroscopy of brain) were used in order to monitor metabolic responses to the drug. One week of DCA treatment produced significant decreases (p < 0.05) in blood lact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
0
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(87 citation statements)
references
References 3 publications
5
80
0
2
Order By: Relevance
“…Only two studies have demonstrated reductions in the Choline/Creatine ratio in mitochondrial patients (Bianchi et al, 2003;De Stefano, 1995). The limited data may reflect that choline in the 1 H spectrum represents the sum of both membrane precursors and catabolytes; since these components may not change in opposite directions; the sum may provide a negligible index of change.…”
Section: Other Brainmentioning
confidence: 99%
“…Only two studies have demonstrated reductions in the Choline/Creatine ratio in mitochondrial patients (Bianchi et al, 2003;De Stefano, 1995). The limited data may reflect that choline in the 1 H spectrum represents the sum of both membrane precursors and catabolytes; since these components may not change in opposite directions; the sum may provide a negligible index of change.…”
Section: Other Brainmentioning
confidence: 99%
“…Pathologic accumulation (resonance at 1.3 ppm) of this end product of anaerobe glycolysis indicates that oxidative metabolism is unable to meet energy requirements. Neurological diseases accompanied by positive lactate findings in MRS are, e.g., hypoxia, ischemia, epilepsy, tumors, and mitochondrial diseases (1,7,8,14,20).…”
Section: Compounds Observable In Vivomentioning
confidence: 99%
“…Dichloroacetate has been studied in small numbers of patients with mitochondrial myopathies, chronic progressive external ophthalmoplegia, Kearne-Sayre syndrome, Leigh syndrome, mitochondrial encephalopathy lactic acidosis and stroke-like episodes (MELAS), congenital lactic acidosis, and 1 patient with a mtDNA depletion syndrome [16][17][18][19]. Most of the studies have included children and adults with multiple mitochondrial disorders, making results difficult to interpret.…”
Section: Dichloroacetatementioning
confidence: 99%
“…Study designs have been double blind, placebocontrolled crossover trials with washout periods of various lengths between study arms [16][17][18][19]. Statistically significant decreases in blood lactate, pyruvate, and alanine at rest and after exercise and improvements on brain MRS, including a reduction of the brain lactate/creatine ratio, increase in brain choline/ creatine ratio, and statistically significant increase in the N-acetyl aspartate (NAA)/creatine ratio, have been reported in some, but not all, studies [16,17]. A single study including only adults with the common MELAS mutation 3243A>G mtDNA was discontinued owing to peripheral nerve toxicity.…”
Section: Dichloroacetatementioning
confidence: 99%